P36 Is it feasible to evaluate cardiac mri in patients who activate the primary percutaneous coronary intervention pathway using hospital episode statistics data?. (2nd September 2017) - Pufulete, M; Harris, J; Dorman, S; Brierley, R; Reeves, B
Abstract : Background: Cardiac magnetic resonance (CMR) imaging is a non-invasive test used to assess the structure and function of the heart. We tested the feasibility of assembling a retrospective cohort study of patients who activate the primary percutaneous coronary intervention (PPCI) pathway using data from Hospital Episode Statistics (HES) and Patient Episode Database Wales (PEDW) to: i) document the use of cardiac magnetic resonance (CMR) imaging in this population; and ii) determine whether CMR is associated with improved clinical outcomes. Methods: Patients from four UK sites were recruited into the prospective cohort study. We assembled a database by linking routinely collected hospital data for the index PPCI admission (demography, clinical, biochemistry and imaging) with HES and PEDW describing inpatient and outpatient NHS episodes in the 12 months following the index PPCI admission. We determined whether we could identify the following from HES/PEDW data: i) the index event (cohort entry); ii) CMR within 10 weeks of the index event (exposure); iii) relevant subgroups of the population (e.g. PPCI, unobstructed coronary arteries, multivessel disease, cardiac arrest, etc.); and iv) clinical outcomes. Results: A total of 1670 patients were recruited prospectively into the cohort study; of these 1612 (97%) had admission data in HES/PEDW that coincided with the index event (±1 day). Only 1227/1612 (76%) had HES/PEDW data that met the criteria for cohort entry; 1110 (91%) were identified as PPCI and 117 (9%) were identified as emergency angiography only. The remainder (385/1612, 24%) did not meet inclusion criteria (PCI procedure code and ST-elevation myocardial infarction, STEMI, diagnostic code) or their angiography was not identified as an emergency. Hospital data documented that 187 patients had CMR but, in the HES/PEDW data (inpatient and outpatient), CMR was recorded for only 53 of these (28%). We are currently exploring algorithms to identify specific subgroups of particular interest with respect to CMR; early results suggest that we can identify patients who have had cardiac arrest or who have unobstructed arteries but not those with multivessel disease. Conclusion: It is possible to identify patients who activate the PPCI pathway from routinely collected HES/PEDW data. We conclude that it is not currently feasible to document the use of CMR in patients who activate the PPCI pathway from HES/PEDW data although the integration of the Diagnostic Imaging Dataset with inpatient and outpatient HES datasets may make it feasible soon. We are exploring the reasons for the discordance between CMR scans reported in the prospective cohort study and those identified in HES.